The contribution of postural balance analysis in older adult fallers: A narrative review. Issue 2 (April 2016) - Pizzigalli, L.; Micheletti Cremasco, M.; Mulasso, A.; Rainoldi, A.
Summary: Objective: Falls are a serious health problem for older adults. Several studies have identified the decline of postural balance as one of the main risk factors for falls. Contrary to what may be believed, the capability of force platform measurements to predict falls remains uncertain. The focus of this narrative review is the identification of postural characteristics of older adults at risk of falling using both static and dynamic postural balance assessments. Methods: The literature analysis was conducted on Medline/PubMed. The search ended in May 2015. Results: Centre of pressure (CoP) path length, CoP velocity and sway in medial lateral and anterior-posterior are the variables that distinguish older adult fallers from non-fallers. Discussion: Recommendations to medical personnel on how to provide efficient balance training for older adults are offered, discussing the relevance and limitations of postural stability on static and dynamic board in falling risk prevention.